The Ethiopian Statutory Rape Law in Light of Human Rights Approach - Ashine, Enguday Meskele (2020)
Statutory rape refers to sexual relations involving someone below the "age of consent." People below the age of consent cannot legally consent to having sex. This means that sex with them, by definition, violates the law. Statutory rape laws vary by state, with states setting the age of consent differently, as well as using different names to refer to this crime. Ethiopian statutory rape provided under laws addressing injury to sexual liberty and chastity. This article will examine the Ethiopian statutory rape law in light of human right approach. During the investigation of the Federal Supreme Court Cassation Division Decision, the constitution of Ethiopian and international human right instruments shows that this statutory provision violate the victims and the defendants human right. Keywords: human right, rape, statutory, sexuality. DOI: 10.7176/JLPG/97-01 Publication date:May 31st 202